Bacterial Abundance and Identification in Recirculating System of Sumatran Barb Fish Rearing Media with Duckweed as Biofilter - Dita Wisudyawati; Ardha Nur Mustofa; Fajri Rahman Afif; Dinzidan Adiputra; Fata Habiburrahman; Md Afsar Ahmed Sumon; Abdul Manan; Rozi; Muhammad Hanif Azhar (Universitas Islam Lamongan, 2026)
The Sumatran Barb fish (Puntigrus tetrazona) is a freshwater ornamental fish which is highly demanded in the ornamental fish export market for its attractive colour patterns. The common problem in ornamental fish farming is the excessive use of water resources, increasing operational costs. A Recirculating Aquaculture System (RAS) is preferred since it can process water repeatedly and is more environmentally friendly. Duckweed plants (Lemna minor) can be used as a natural biofilter because they absorb nutrients such as nitrogen and phosphorus and provide a habitat for beneficial bacteria. This study was conducted for 40 days, with the treatments consisting of different plant coverage areas. Duckweed plants were applied with area coverage of P0/control (without duckweed plant), P1 (20% area coverage of duckweed plants), P2 (40% area coverage of duckweed plants), and P3 (60% area coverage of duckweed plants). The bacterial abundance values obtained during the maintenance period ranged from 1.52 to 1.79 x 106 CFU mL-1 and differed significantly (P<0.05) across all treatments. The lowest TPC value was observed in the P0 treatment (1.52 x 106 CFU mL-1), and the highest in the P2 treatment (1.79 x 106 CFU mL-1). Based on the identification test, bacteria belonging to the genera Neisseria, Acinetobacter, Nitrosomonas, and Pseudomonas were identified. Water quality parameters were optimal across all treatments, namely pH between 6.0 and 6.85, dissolved oxygen (3.43-3.95 mg L-1), TAN (0.2-0.4 mg L-1), and phosphate (1.00-2.5 mg L-1). Meanwhile, temperature and nitrate exceeded the optimal limits, with values ranging from 29 to 30 °C and 72 to 210 mg L-1 across all treatments.